Thread-safety in an MPI implementation: Requirements and analysis - Gropp, William; Thakur, Rajeev (Parallel computing, 2007)
The MPI-2 Standard has carefully specified the interaction between MPI and user-created threads. The goal of this specification is to allow users to write multithreaded MPI programs while also allowing MPI implementations to deliver high performance. However, a simple reading of the thread-safety specification does not reveal what its implications are for an implementation and what implementers must be aware (and careful) of. In this paper, we describe and analyze what the MPI Standard says about thread-safety and what it implies for an implementation. We classify the MPI functions based on their thread-safety requirements and discuss several issues to consider when implementing thread-safety in MPI. We use the example of generating new context ids (required for creating new communicators) to demonstrate how a simple solution for the single-threaded case does not naturally extend to the multithreaded case and how a naïve thread-safe algorithm can be expensive. We then present an algorithm for generating context ids that works efficiently in both single-threaded and multithreaded cases.